Role of Raf Kinase Inhibitor Protein in Hepatocellular Carcinoma - Walker, Evan J. (2011)
Hepatocellular carcinoma (HCC) accounts for 80–90% of primary liver tumors and is one of the most common and devastating malignant diseases worldwide. The MAPK signaling pathway is activated in over 90% of HCCs, and RKIP has been identified as an inhibitor of the MAPK pathway. It has been observed that downregulation of RKIP expression in HCC tumors contributes to constitutive activation of the ERK/MAPK pathway and promotes proliferation and migration of HCC cells. More important, activation of IGF-I/ERK/MAPK pathways can be blocked by restoration of RKIP levels. The protein levels of RKIP are significantly reduced in HCC, whereas mRNA levels only decreased in 41% of HCC samples studied, suggesting that the downregulation of RKIP in HCC may be influenced through multiple mechanisms both at the mRNA and protein levels. In this context, mTOR inhibitor, insulin, and proteasome inhibitors were found to modulate RKIP expression in FOCUS HCC cells. A better understating of mechanisms by which RKIP expression is downregulated in HCC may be critical to develop a possible target for therapeutic intervention of HCC.